The magnetotherapy delusion. - Arias, A. González (Revista Cubana de Física, 2007)
In recent years there has been a "resurrection" of the so-called magnetic therapies, based on the application of permanent magnets in different parts of the body. The widespread application of these "therapies", as well as the distribution of false information connected to the subject, have led us to think that the hoax should be exposed, or at least mentioned, in the courses of basic physics. Some detailed arguments stressing the physics on the subject are discussed, with the feeling that the information could be helpful for all those who teach physics in science and engineering. It is recalled that a magnetostatic field cannot transfer magnetic energy to moving charged particles, showing the falsehood of some statements appearing in the pseudoscientific literature. Disregard of the history of medicine as well as scientific methods and bioethics could be the explanation of why some of these therapies are so far claimed as valuable for some people.